Single Particle Assays to Determine Heterogeneities within Fluid Catalytic Cracking Catalysts - Nieuwelink, Anne Eva; Velthoen, Marjolein E.Z.; Nederstigt, Yoni C.M.; Jagtenberg, Kristel L.; Meirer, Florian; Weckhuysen, Bert M. (John Wiley and Sons Inc., 2020)
Invited for the cover of this issue is the group of Bert M. Weckhuysen at Utrecht University. The image depicts an artistic impression of catalyst particles in full color: by combining multiple characterization techniques per single Fluid Catalytic Cracking (FCC) particle, insights are provided into the heterogeneity of an industrially used catalyst. Read the full text of the article at 10.1002/chem.201905880.
Keywords: Taverne; Catalysis; Organic Chemistry